The Interaction Between StCDPK14 and StRbohB Contributes to Benzo-(1, 2, 3)-Thiadiazole-7-Carbothioic Acid S-Methyl Ester-Induced Wound Healing of Potato Tubers by Regulating Reactive Oxygen Species Generation - Ma, Li; Jiang, Hong; Bi, Yang; Li, Yong-Cai; Yang, Jiang-Wei; Si, Huai-Jun; Ren, Ying-Yue; Prusky, Dov (Frontiers in Plant Science, 2021)
Reactive oxygen species (ROS) production is essential for both physiological processes and environmental stress in diverse plants. Previous studies have found that benzo-(1, 2, 3)-thiadiazole-7-carbothioic acid S-methyl ester (BTH)-inducible ROS were associated with wound healing of potato tubers. Calcium-dependent protein kinases (CDPKs), the important calcium receptors, are known to play a crucial part in plant development and adaptation to abiotic stresses. However, whether CDPK-mediated ROS generation induced by BTH is involved in wound healing is elusive. In this study, we measured Solanum tuberosum CDPKs (StCDPKs) expression using real-time PCR, and it was found that the transcriptional levels of StCDPKs from BTH-treated tissues were significantly induced, among which StCDPK14 presented the most increased level. Subcellular localization results showed that StCDPK14 is located in the nucleus and membrane. The transgenic potato plants and tubers were developed using interference-expression of StCDPK14 by Agrobacterium tumefaciens–mediated transformation. The St respiratory burst oxidase homologs (StRbohs) expression showed a remarkable decrease in StCDPK14 transgenic tubers, notably, H2O2 content and suberin deposition were also significantly declined. To confirm the relationship between StCDPK14 and StRbohB, yeast-two-hybrid and bimolecular fluorescence complementation were used to examine the interaction, and it was shown that StCDPK14 interacted with the specific Ca2 + -binding motif (helix-loop-helix, called EF-hand) of StRbohB N-terminus. The above results unraveled that StCDPK14 functions in ROS generation via interacting with StRbohB during wound healing of potato tubers.